THE EFFECT OF SOCIAL MEDIA USE ON STUDENTS' LEARNING MOTIVATION AT SMPN 3 NATAL - Rizkiyah Pusrnama; Dewi candra (Rahis Cendekia Indonesia, 2024)
This study aims to analyze the effect of social media use on learning motivation of students at SMPN 3 Natal. The method used is quantitative descriptive with a survey approach to 100 students. The results of the study indicate that students who use social media wisely have higher learning motivation. However, excessive use has a negative impact on concentration and academic achievement. In conclusion, social media can be an effective learning tool if used properly..